2016
DOI: 10.1016/j.cmi.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro activity of oral antimicrobial agents against Enterobacteriaceae from patients with community-acquired urinary tract infections in three European countries

Abstract: Enterobacteriaceae causing community-acquired urinary tract infections were examined in selected outpatient clinics and hospitals in Belgium, Germany and Spain using EUCAST breakpoints for susceptibility. A total of 1190 isolates were collected. Escherichia coli isolates were resistant to amoxicillin-clavulanic acid (28.1%), ciprofloxacin (23.4%) and trimethoprim-sulfamethoxazole (21.4%) compared with fosfomycin and nitrofurantoin (each, <1.5%). Ceftibuten (MIC50/90 0.25/0.5 mg/L) and ceftriaxone activity (MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 15 publications
1
29
1
3
Order By: Relevance
“…In the present investigation, a genotypically diverse population of Enterobacteriaceae isolates (including those expressing CTX-M as well as TEM and SHV ␤-lactamases of wild types and ESBL types) at the upper end of the CTB MIC distribution with MICs of 1 to Ͼ32 mg/liter (MIC 90 of Յ0.5 mg/liter among Enterobacteriaceae [15]) was chosen to represent the most challenging clinical potentialities. Multifold reductions in MICs were noted in the presence of CLA relative to the MICs of CTB alone; thereby, CLA restored the activity of CTB and improved its stability against hydrolysis in the presence of ␤-lactamase-producing isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present investigation, a genotypically diverse population of Enterobacteriaceae isolates (including those expressing CTX-M as well as TEM and SHV ␤-lactamases of wild types and ESBL types) at the upper end of the CTB MIC distribution with MICs of 1 to Ͼ32 mg/liter (MIC 90 of Յ0.5 mg/liter among Enterobacteriaceae [15]) was chosen to represent the most challenging clinical potentialities. Multifold reductions in MICs were noted in the presence of CLA relative to the MICs of CTB alone; thereby, CLA restored the activity of CTB and improved its stability against hydrolysis in the presence of ␤-lactamase-producing isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of human-simulated CTB-CLA exposures resulted in net stasis in vivo among the majority of the isolates examined, with combination CTB-CLA (2:1 ratio) MICs of Յ4 mg/liter, inclusive of those with CTB MICs of Ͼ32 mg/liter. The pharmacodynamic target of stasis in preclinical infection models is generally considered a surrogate endpoint for prediction of clinical efficacy in UTI, in contrast to a more deep-seeded infection (e.g., pneumonia), as drug accumulation in the bladder produces exposures that are severalfold higher than the plasma drug concentrations as well as the MICs for the causative organisms (15,16). This has subsequently been shown to translate to good clinical efficacy, specifically in the context of treatment with cephalosporins for complicated UTs (cUTIs) attributed to ESBL producers (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…susceptibility to FOS. Some studies have reported a low resistance rate, even among hospital‐acquired infections, whereas others have reported resistance rates of up to 60% …”
Section: Discussionmentioning
confidence: 99%
“…susceptibility to FOS. Some studies have reported a low resistance rate, even among hospital-acquired infections,[38][39][40] whereas others have reported resistance rates of up to 60% [41][42][43][44][45][46]. The E. coli and E. faecalis isolates showed greater susceptibility to FOS, which could explain the reduced incidence of UTI due to E. coli in Group 1 (n = 4, 12.5% vs n = 12, 34.3%; P = 0.047) and the absence of events caused by E. faecalis in the same group.Strikingly, both bacteria were susceptible to FOS despite patient exposure during the clinical trial; similar findings have been reported when searching for FOS-resistant mutations during therapy 47,48.…”
mentioning
confidence: 99%
“…Так, среди возбудителей, представляющих суммарно ~ 40% общей структуры, более 30% штаммов Klebsiella spp. и 26,1% штаммов P. mirabilis были устойчивы к данному препарату [6].…”
unclassified